FUNGSI HUKUM NOTA KESEPAHAMAN SEBAGAI PERIKATAN PERJANJIAN MENURUT KITAB UNDANG-UNDANG HUKUM PERDATA (KUH PERDATA) - Mochamad Moro Asih; Tunjung Fitra Wijanarko (Universitas Islam Syekh Yusuf, 2021)
The position of the Memorandum of Understanding on Indonesian Civil Law, as a written form of understanding between the parties, is not a law based agreement. In consequences, no sanctions applied for those parties whose denying (the agreement(s), but on moral sanction. However, a Memorandum of Understanding that does not have a compelling legal force can have it sanctions for any parties involved. The strength to binding (parties) of the Memorandum of Understanding according to agreement law in Indonesia is found on Indonesian Civil Code, equate a Memorandum of Understanding with an “agreement”. Article 1338 of Indonesian Civil Code states that every agreement made, legally binding as a law for the parties who made such agreement (Pacta Sunt Servanda), but if the legal elements of the agreement in Article 1320 Indonesia Civil Law are not fulfilled, then the Memorandum of Understanding is anulled and void by law, and has no legal force. Keywords: Memorandum of Understanding, agreement, sanction, Code of Civil Law